IMF Survey, Volume 36 Issue 10. (IMF Survey; IMF Survey ;, 2007)
IMF work agenda; IMF exchange rate advice; Asia's trade pacts; Central Asia: economic cooperation; Cameroon after debt relief; spread of Austrian banks; conference on financial soundness indicators; Caruana on shifting roles in financial globalization.